Burst wave lithotripsy and acoustic manipulation of stones. Issue 2 (March 2020) - Chen, Tony T.; Samson, Patrick C.; Sorensen, Mathew D.; Bailey, Michael R.
Abstract : Purpose of review: Burst wave lithotripsy and ultrasonic propulsion of kidney stones are novel, noninvasive emerging technologies to separately or synergistically fragment and reposition stones in an office setting. The purpose of this review is to discuss the latest refinements in technology, to update on testing of safety and efficacy, and to review future applications. Recent findings: Burst wave lithotripsy produced consistent, small passable fragments through transcutaneous applications in a porcine model, while producing minimal injury and clinical trials are now underway. A more efficient ultrasonic propulsion design that can also deliver burst wave lithotripsy effectively repositioned 95% of stones in 18 human participants (18 of 19 kidneys) and clinical trials continue. Acoustic tractor beam technology is an emerging technology with promising clinical applications through the manipulation of macroscopic objects. Summary: The goal of the reviewed work is an office-based system to image, fragment, and reposition urinary stones to facilitate their natural passage. The review highlights progress in establishing safety, effectiveness, and clinical benefit of these new technologies. The work is also anticipating challenges in clinical trials and developing the next generation of technology to improve on the technology as it is being commercialized today.